Renaissance and revenants in an emerging global city: discourses of heritage and urban design in Cape Town's District One and District Six, 2002-2014 - Ernsten, Christian (African Studies, 2017)
On 10 January 2014, the New York Times placed Cape Town at the top of its list of the "52 places to go in 2014". The hopeful rhetoric of the city as ultimate holiday destination, African creative metropolis, prime global-events location and city of freedom indicates powerful cultural discourses at work. Looking at how Cape Town is simultaneously reinvented and haunted, this thesis poses a set of questions regarding the discourses associated with the reinvention of the city, on the one hand, and the city's unresolved pasts, on the other. Situated at the convergence of two fields, Urban Studies and Heritage Studies, it sets out to investigate the workings of heritage and urban-design discourses in the city of Cape Town over the period of 2002 to 2014. It describes the unfolding of these discourses, and discusses the organisational process of both the 2010 FIFA World Cup and the 2014 World Design Capital in relation to the exhumation of human remains at District One and the restitution of land at District Six. Using as its methodology a combination of embedded ethnographic research, qualitative indepth interviews, desktop and archival research, and a form of embodied research, the thesis points to a historical hinge upon which these discourses shift. Through discourse analysis, it examines what this discursive shift entails, and how it takes place. It points to "moments of poignancy" in the construction of Cape Town's recent urban transformation. As such, this study offers a series of insights into the links between colonial modernity, on the one hand, and the origins of contemporary heritage and urban-design discourses in Cape Town, on the other. It examines the function of official discourse concerning the design of the city, as well as the sudden eruptions of public dissent that disturb this official discourse. The central argument of this thesis is that, through an in-depth understanding of the shifts, transformations and internal workings of the discourses of heritage and urban design, a critique can be made of the way contemporary Cape Town has been repositioned in relation to the city's past, present and future.